Orientowanie się w przestrzeni bez przestrzeni – o budowaniu świadomości przestrzennej w edukacji wczesnoszkolnej - Marzenna Nowicka (Problemy Wczesnej Edukacji)
Orientation in physical space is a skill that allows functioning well in everyday life. The task of the school is to support this skill. The article presents the results of an analysis of 3 packages of school textbooks intended for I–III classes of primary school. It was agreed that textbook instructions concerning building spatial awareness are of a narrow instrumental nature and are focused solely on achieving efficiency in school understanding. The focus is on static situations organized in the classroom and exercises on the plane. Children acquire only knowledge about space, and do not accumulate useful experience related to everyday functioning in it.